Semiautomatic method for the ultra-trace arsenic speciation in environmental and biological samples via magnetic solid phase extraction prior to HPLC-ICP-MS determination - Montoro-Leal, Pablo; García-Mesa, Juan Carlos; Morales-Benítez, Irene; García-de-Torres, Amparo; Vereda-Alonso, Elisa Isabel (Elsevier B.V., 2021)
A novel magnetic functionalized material based on graphene oxide and magnetic nanoparticles (MGO) was used to develop a magnetic solid phase extraction method (MSPE) to enrich both, inorganic and organic arsenic species in environmental waters and biological samples. An automatic flow injection (FI) system was used to preconcentrate the arsenic species simultaneously, while the ultra-trace separation and determination of arsenobetaine (AsBet), cacodylate, AsIII and AsV species were achieved by high performance liquid chromatog raphy combined with inductively coupled plasma mass spectrometry (HPLC-ICP-MS). The sample was introduced in the FI system where the MSPE was performed, then 1 mL of eluent was collected in a chromatographic vial, which was introduced in the autosampler of HPLC-ICP-MS. Therefore, preconcentration and separation/deter mination processes were automatic and conducted separately. To the best of our knowledge, this is the first method combining an automatic MSPE with HPLC-ICP-MS for arsenic speciation, using a magnetic nanomaterial based on MGO for automatic MSPE. Under the optimized conditions, the LODs for the arsenic species were 3.8 ng L− 1 AsBet, 0.5 ng L− 1 cacodylate, 1.1 ng L− 1 AsIII and 0.2 ng L− 1 AsV with RSDs <5%. The developed method was validated by analyzing Certified Reference Materials for total As concentration (fortified lake water TMDA 64.3 and seawater CASS-6 NRC) and also by recovery analysis of the arsenic species in urine, well-water and seawater samples collected in Malaga. ´ The developed method has shown promise for routine monitoring of arsenic species in environmental waters and biological fluids.
Keywords: Materiales magnéticos; Grafeno; Nanopartículas; Arsenic speciation; Magnetic graphene oxide; Solid phase extraction; HPLC-ICP-MS